Challenges Regarding Boundaries Between Work And Personal Life Due To Always Connected Technology: Tantangan Mengenai Batasan Antara Pekerjaan Dan Kehidupan Pribadi Akibat Tekhnologi Yang Selalu Terkoneksi - Maharani Resti Marinda; Meri Dian Nisa; Luluk Afifah; Choiron Ramdhan; M. Isa Anshori (Institute of Educational, Research, and Community Service, 2023)
This study emphasises the importance of realising and maintaining work-life balance in today's work environment. This chapter outlines what this balance means, examines how it affects individual well-being and organisational productivity, and describes the factors that influence it. We also discuss ways to achieve better balance in daily routines, including work flexibility, time management and social support. The digital age has brought significant changes to the way we work and live our daily lives. As technology advances, the concept of work-life balance is becoming increasingly important in both professional and personal life. This article explains the main challenges that individuals face in achieving work-life balance in the digital age, and provides solutions that can help overcome these challenges